Electroless plating primer containing polymer and metal particles
Patent Information
- Application Number
- JP2022501817
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-19
- Filing Date
- 2021-02-08
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-02-08
AI Technical Summary
【0008】 本発明の下地剤は、基材上に塗布するだけで容易に無電解めっきの下地層を形成することができる。また本発明によれば、基板への密着性に優れ、めっきの析出性を影響しないめっきの下地層を形成することができる。しかも本発明の下地剤は、様々な組成にて容易にワニス化が可能であり、高い金属微粒子分散安定性を有するものとすることができる。 さらに、本発明の下地剤に使用するポリマーは、少ないプロセスで簡便に調製可能であることから、めっき下地剤の製造工程の簡略化と製造コストの低減も図ることができる。 また、本発明の無電解めっき下地剤から形成された無電解金属めっきの下地層は、無電解めっき浴に浸漬するだけで、容易に金属めっき膜を形成でき、基材と下地層、そして金属めっき膜とを備える金属被膜基材を容易に得ることができる。 すなわち、本発明の密着性を付与するベース樹脂が配合されているめっき下地剤を用いても、基材上に優れためっき析出性を発現する下地層を形成することができる。
Smart Images

Figure 0007652183000001 
Figure 0007652183000002 
Figure 0007652183000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electroless plating undercoat agent containing a polymer and fine metal particles. [Background technology]
[0002] Electroless plating can be used to obtain a coating of uniform thickness regardless of the type or shape of the substrate by simply immersing the substrate in a plating solution, and can form a metal plating film even on non-conductive materials such as plastic, ceramic, and glass. As a result, electroless plating is widely used in a variety of fields, including decorative applications such as imparting a luxurious and aesthetic feel to resin molded articles such as automobile parts, electromagnetic shielding, and wiring technologies for printed circuit boards and large-scale integrated circuits. Usually, when a metal plating film is formed on a substrate (subject to be plated) by electroless plating, a pretreatment is carried out to improve the adhesion between the substrate and the metal plating film. Specifically, the surface to be treated is first roughened and / or hydrophilized by various etching means, and then a sensitization treatment is carried out in which an adsorbent material that promotes the adsorption of the plating catalyst onto the surface to be treated is supplied to the surface to be treated, and an activation treatment is carried out in which the plating catalyst is adsorbed onto the surface to be treated. Typically, the sensitization treatment is carried out by immersing the substrate to be treated in an acidic solution of stannous chloride, which causes the metal (Sn) that can act as a reducing agent to be adsorbed onto the surface to be activated. 2+ ) adheres to the surface to be treated. The surface to be treated is then immersed in an acidic solution of palladium chloride as an activation treatment. This converts the palladium ions in the solution into reducing metals (tin ions: Sn 2+ ) and are attached to the surface to be treated as active palladium catalytic nuclei. After such pretreatment, the surface is immersed in an electroless plating solution to form a metal plating film on the surface to be treated.
[0003] In response to this, a case has been reported in which a composition containing a hyperbranched polymer having ammonium groups and metal fine particles has been used as a primer (plating catalyst) for electroless plating. This has been proposed as an electroless plating primer that aims to achieve various improvements in terms of the environment, costs, and cumbersome operability, such as avoiding the use of chromium compounds (chromic acid), which has been a problem in the pretreatment step (surface roughening treatment) of conventional electroless plating processes, and reducing the number of pretreatment steps (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Patent Application Publication No. 2012 / 141215 Brochure Summary of the Invention [Problem to be solved by the invention]
[0005] In the compositions containing various hyperbranched polymers and metal fine particles proposed as the above-mentioned primers for electroless plating, it is necessary to add other base resins having the respective functions in order to impart other functions (e.g., adhesion, heat resistance, photosensitivity, dielectric properties, etc.) to the substrate. However, the above-mentioned primers may significantly impair the deposition properties of plating if they contain other base resins that do not function as a plating primer. In other words, the electroless plating primers containing hyperbranched polymers and metal fine particles proposed thus far have had the problem that the plating deposition properties may be reduced when another base resin that does not function as a plating primer is added. The present invention has been made to solve the above-mentioned problems, and aims to provide a plating primer that can form a plating primer layer exhibiting excellent plating deposition properties even when a plating primer containing a base resin that imparts adhesion is used. Another aim of the present invention is to provide a new primer that can be used as a pretreatment step for electroless plating and can realize low cost in its production. [Means for solving the problem]
[0006] Means for Solving the Problems The present inventors have conducted intensive research in order to achieve the above-mentioned object, and have found that a polymer containing fluorine atoms, specifically a polymer having a trifluoromethyl group and a metal-dispersing group in the molecule, has excellent metal dispersibility, and that a layer obtained by combining this polymer with metal fine particles and applying the resulting layer onto a substrate has excellent plating properties as an underlayer for electroless metal plating, thus completing the present invention.
[0007] That is, according to a first aspect, the present invention provides an electroless plating undercoat agent for forming a metal plating film on a substrate by electroless plating treatment, comprising: (A) a copolymer containing a structural unit derived from a monomer a having at least one trifluoromethyl group and one radically polymerizable double bond in the molecule, and a structural unit derived from a monomer b having a metal dispersing group and one radically polymerizable double bond in the molecule; (B) metal particles, and (C) Solvent The present invention relates to a primer comprising the above compound. As a second aspect, the present invention relates to the base agent according to the first aspect, which contains a complex in which the (B) metal fine particles are attached to or coordinated to the metal-dispersing groups in the (A) copolymer. As a third aspect, the present invention relates to the base agent according to the first or second aspect, in which the monomer a is a compound having either a vinyl group or a (meth)acryloyl group. As a fourth aspect, the present invention relates to the base agent according to the third aspect, in which the monomer a is a compound represented by the following formula (1): [ka] In formula (1), M represents a single bond, a carbonyloxy group, an amide group, or a phenylene group, J represents a linear or branched alkyl group having 1 to 10 carbon atoms and at least one trifluoromethyl group, R 6represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.) As a fifth aspect, the present invention relates to the base material according to the first aspect or the second aspect, in which the monomer b is a compound having either a vinyl group or a (meth)acryloyl group. As a sixth aspect, the present invention relates to the base agent according to the fifth aspect, in which the monomer b is a compound represented by the following formula (2) or (3): [ka] (In formula (2), R1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, L represents O or N, and R2 is present only when L represents N and represents a hydrogen atom, or R1 and R2 may form a 4- to 6-membered cyclic amide together with the atom to which they are bonded. In formula (3), R3 represents a hydrogen atom or a methyl group. R4 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be branched, an alkoxyl group having 1 to 10 carbon atoms which may be branched, or an alkoxylalkyl group having 1 to 10 carbon atoms which may be branched; L represents O or N; R5 is present only when L represents N and represents a hydrogen atom; or R4 and R5 may form, together with the atom to which they are bonded, a 4- to 6-membered cyclic amide or a 4- to 6-membered cyclic imide. As a seventh aspect, the present invention relates to the base agent according to the sixth aspect, in which the monomer b is N-vinylpyrrolidone, N-vinylacetamide, or N-vinylformamide. As an eighth aspect, the present invention relates to the base agent according to any one of the first to seventh aspects, in which the monomer mixture that gives the (A) copolymer contains the monomer a in an amount that is 5 to 500% by mole of the monomer b. As a ninth aspect, the present invention relates to the base agent according to any one of the first to eighth aspects, in which the copolymer (A) further contains a structural unit derived from a monomer c having a crosslinkable group and one radically polymerizable double bond in the molecule. As a tenth aspect, the present invention relates to the base agent according to the ninth aspect, in which the monomer c is a compound having either a vinyl group or a (meth)acryloyl group. According to an eleventh aspect, the present invention relates to the base agent according to the tenth aspect, in which the monomer c is a compound represented by the following formula (4): [ka] (In formula (4), X represents a single bond, a carbonyloxy group, an amide group or a phenylene group; Y represents an alkylene group having 1 to 6 carbon atoms, an oxyalkylene group having 1 to 6 carbon atoms, an optionally branched alkyl ether group having 1 to 6 carbon atoms, a thioalkylene group having 1 to 6 carbon atoms or a thioalkyl ether group having 1 to 6 carbon atoms; Z represents a crosslinkable group; R 7 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. As a twelfth aspect, the present invention relates to the base agent according to any one of the ninth to eleventh aspects, in which the monomer mixture which gives the (A) copolymer contains the monomer c in an amount that is 5 to 300% in molar amount relative to the molar amount of the monomer b. As a thirteenth aspect, the present invention relates to the primer according to any one of the first to twelfth aspects, in which the (B) metal microparticles are microparticles of at least one metal selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), tin (Sn), platinum (Pt), and gold (Au). According to a fourteenth aspect, the present invention relates to the undercoat agent according to the thirteenth aspect, in which the (B) metal fine particles are palladium fine particles. According to a fifteenth aspect, the present invention relates to the base agent according to any one of the first to fourteenth aspects, in which the (B) metal fine particles are fine particles having an average primary particle size of 1 to 100 nm. As a sixteenth aspect, the present invention relates to the base agent according to any one of the first to fifteenth aspects, further comprising (D) a base resin having a non-radically polymerizable crosslinkable group. As a seventeenth aspect, the present invention relates to the base material according to any one of the first to sixteenth aspects, further comprising (E) a crosslinking agent. According to an eighteenth aspect, the present invention relates to an underlayer for electroless metal plating, which is made of a film containing the electroless plating undercoat agent according to any one of the first to seventeenth aspects. As a nineteenth aspect, the present invention relates to a metal plating film formed on the electroless metal plating underlayer according to the eighteenth aspect. As a twentieth aspect, the present invention relates to a metal-coated substrate comprising a substrate, an underlayer of electroless metal plating according to the eighteenth aspect formed on the substrate, and a metal plating film formed on the underlayer of electroless metal plating. As a twenty-first aspect, the present invention relates to a method for producing a metal-coated substrate, the method including the following steps (1) and (2): (1) step: applying the electroless plating primer according to any one of the first to seventeenth aspects onto a substrate to form a substrate layer for electroless metal plating on the substrate; Step (2): A step of immersing the substrate on which the underlayer has been formed in an electroless plating bath to form a metal plating film on the underlayer. Effect of the Invention
[0008] The primer of the present invention can be easily applied to a substrate without any electrical wiring. untie It is possible to form a base layer for plating. Furthermore, according to the present invention, it is possible to form a base layer for plating that has excellent adhesion to a substrate and does not affect the deposition of plating. Furthermore, the base agent of the present invention can be easily made into a varnish with various compositions and can have high dispersion stability of metal fine particles. Furthermore, since the polymer used in the undercoat agent of the present invention can be easily prepared with a few steps, it is possible to simplify the manufacturing process of the plating undercoat agent and reduce the manufacturing cost. Furthermore, the electroless metal plating underlayer formed from the electroless plating primer of the present invention can easily form a metal plating film by simply immersing it in an electroless plating bath, making it easy to obtain a metal-coated substrate comprising a substrate, an underlayer, and a metal plating film. That is, even when the plating primer containing the base resin of the present invention that imparts adhesion is used, a primer layer that exhibits excellent plating deposition properties can be formed on a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. The primer of the present invention contains (A) a copolymer having the specific structural units described above, (B) fine metal particles, and (C) a solvent, and may contain other components as necessary. The undercoat agent of the present invention is suitably used as a catalyst for forming a metal plating film on a substrate by electroless plating treatment. Each component will be described below. <(A) Copolymer>
[0010] Component (A) is a copolymer containing a structural unit derived from monomer a having a crosslinkable group and one radically polymerizable double bond in its molecule, and a structural unit derived from monomer b having a metal dispersing group and one radically polymerizable double bond in its molecule.
[0011] [Monomer a] Monomer a is a monomer having at least one trifluoromethyl group and one radically polymerizable double bond in the molecule.
[0012] A specific example of the monomer a is a compound represented by the following formula (1). [ka] In formula (1), M represents a single bond, a carbonyloxy group, an amide group, or a phenylene group, J represents a linear or branched alkyl group having 1 to 10 carbon atoms and at least one trifluoromethyl group, R 6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. When M represents a carbonyloxy group or an amide group, it can have structures of the following formulae (1-1) to (1-3), with the structure of formula (1-1) being preferred. [ka]
[0013] Examples of J include a perfluoromethyl group (i.e., a trifluoromethyl group), a perfluoroethyl group, a 2,2,2-trifluoroethyl group, a 1,1,2,2,2-pentafluoroethyl group, a 2,2,2-trifluoro-1-(trifluoromethyl)ethyl group, a perfluoropropyl group, a 3,3,3-trifluoropropyl group, a 2,2,3,3,3-pentafluoropropyl group, a 1,1,2,2,3,3,3-heptafluoropropyl group, a hexafluoroisopropyl group, a perfluorobutyl group, a 4,4,4-trifluorobutyl group, a 3,3,4,4,4-pentafluorobutyl group, a 2,2,3,3,4,4,4-heptafluorobutyl group, a 1,1,2,2,3,3,4,4,4-nonafluorobutyl group, and a 2-(perfluorohexyl)ethyl group. Among these, J is preferably a 2,2,2-trifluoroethyl group, a hexafluoroisopropyl group, or a 2-(perfluorohexyl)ethyl group.
[0014] Specific examples of such monomer a include, but are not limited to, the following: 2,2,2-trifluoroethyl acrylate, hexafluoro-2-propyl methacrylate, 2-(perfluorohexyl)ethyl methacrylate, etc.
[0015] [Monomer b] In the present invention, monomer b is a compound having a metal dispersing group and one radically polymerizable double bond in the molecule. The metal dispersing group is a group that improves the dispersibility of the metal fine particles in the composition by interacting with the metal fine particles of component (B) through adhesion and / or coordination, etc., thereby allowing the metal fine particles to exist stably in the composition. As such a metal dispersing group, a substituent having a carbonyl and a moiety having a nitrogen atom covalently bonded thereto, i.e., a -C(=O)-N- moiety, is preferred, and more specifically, a group selected from the group consisting of a group having an amide bond and a group having an imide bond is preferred. The radical polymerizable double bond is preferably a compound having one of either a vinyl group or a (meth)acryloyl group. When the monomer b is a compound having a (meth)acryloyl group as a radical polymerizable double bond, the carbonyl group [-C(=O)-] contained in the (meth)acryloyl group may have a structure overlapping with the carbonyl group in the amide group as the metal dispersing group.
[0016] Specific examples of the monomer b include compounds represented by the following formula (2) or formula (3). [ka] (In formula (2), R1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, L represents O or N, and R2 is present only when L represents N and represents a hydrogen atom, or R1 and R2 may form a 4- to 6-membered cyclic amide together with the atom to which they are bonded. In formula (3), R3 represents a hydrogen atom or a methyl group, R4 represents a hydrogen atom, an optionally branched alkyl group having 1 to 10 carbon atoms, an optionally branched alkoxyl group having 1 to 10 carbon atoms, or an optionally branched alkoxylalkyl group having 1 to 10 carbon atoms, L represents O or N, R5 is present only when L represents N and represents a hydrogen atom, or R4 and R5 may form, together with the atom to which they are bonded, a 4- to 6-membered cyclic amide or a 4- to 6-membered cyclic imide.
[0017] Examples of such monomer b include N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, N-vinylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-butyl(meth)acrylamide, N-isobutyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-octyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-methoxybutyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-isobutoxymethyl(meth)acrylamide, N-isobutoxyethyl(meth)acrylamide, N-vinylphthalimide, and N-vinylsuccinimide.
[0018] Among these, as the monomer b, a monomer represented by formula (2) is preferred from the viewpoint of the coordination ability of the monomer to a metal, a monomer having an N-vinylamide group is more preferred, and in consideration of availability, etc., N-vinylpyrrolidone, N-vinylformamide, and N-vinylacetamide are even more preferred. These monomers b may be used alone or in combination of two or more.
[0019] [Monomer c] The component (A) is also a copolymer that further contains, in addition to monomer a and monomer b, a structural unit derived from monomer c that has a crosslinkable group and one radically polymerizable double bond in the molecule. Examples of the crosslinkable group include an N-alkoxymethyl group, an N-hydroxymethyl group, an epoxy group which may have a substituent Q, an alicyclic epoxy group which may have a substituent Q, and an oxetane group which may have a substituent Q. Examples of the substituent Q include an alkyl group having 1 to 4 carbon atoms which may be substituted by a halogen, and a phenyl group.
[0020] A specific example of the monomer c is a compound represented by the following formula (4). [ka] (In formula (4), X represents a single bond, a carbonyloxy group, an amide group or a phenylene group; Y represents an alkylene group having 1 to 6 carbon atoms, an oxyalkylene group having 1 to 6 carbon atoms, an alkyl ether group having 1 to 6 carbon atoms, a thioalkylene group having 1 to 6 carbon atoms or a thioalkyl ether group having 1 to 6 carbon atoms; Z represents a linear or branched alkyl group having 1 to 10 carbon atoms and having at least one trifluoromethyl group; R 7 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0021] The alkylene group having 1 to 6 carbon atoms represented by Y may be either linear or branched, and specific examples thereof include, but are not limited to, a methylene group, an ethane-1,1-diyl group, an ethane-1,2-diyl group, a propane-1,2-diyl group, a propane-1,3-diyl group, a propane-2,2-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, and the like.
[0022] The oxyalkylene group having 1 to 6 carbon atoms may be linear or branched; -OR 8 - is a group satisfying R 8 Specific examples of the alkylene groups are the same as those of 1 to 6 mentioned above.
[0023] The C1-C6 alkyl ether group may be linear or branched; -R 9 -OR 9 - is a group satisfying R 9 Specific examples of R are not limited to, but each independently includes a methylene group, an ethane-1,1-diyl group, an ethane-1,2-diyl group, a propane-1,2-diyl group, a propane-1,3-diyl group, a propane-2,2-diyl group, a butane-1,4-diyl group, and a pentane-1,5-diyl group. 9 The total number of carbon atoms is 6.
[0024] The thioalkylene group having 1 to 6 carbon atoms may be linear or branched; 8 - is a group satisfying R 8 is as described above.
[0025] The C thioalkyl ether group may be linear or branched, -R 9 -SR 9 - is a group satisfying R 9 is as described above.
[0026] Specific examples of such monomer c include, but are not limited to, the following:
[0027] Examples of the monomer having one radically polymerizable double bond and further having an N-alkoxymethyl group include N-butoxymethylacrylamide, N-isobutoxymethylacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, and N-methylolacrylamide.
[0028] Examples of the monomer having one radically polymerizable double bond and further having an N-hydroxymethyl group include, but are not limited to, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, and the like.
[0029] Examples of monomers having one radically polymerizable double bond and further having an epoxy group include, but are not limited to, glycidyl acrylate, glycidyl methacrylate, α-ethyl acrylate, α-n-propyl acrylate, α-n-butyl acrylate, 3,4-epoxybutyl acrylate, 3,4-epoxybutyl methacrylate, 6,7-epoxyheptyl acrylate, 6,7-epoxyheptyl methacrylate, α-ethyl acrylate, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, 3,4-epoxycyclohexyl methacrylate, etc. Among these, glycidyl methacrylate, 6,7-epoxyheptyl methacrylate, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, 3,4-epoxycyclohexyl methacrylate, etc. are preferably used. These may be used alone or in combination.
[0030] Examples of monomers having one radical polymerizable double bond and further having an oxetane group include, but are not limited to, (meth)acrylic acid esters having an oxetane group. Among such monomers, 3-(methacryloyloxymethyl)oxetane, 3-(acryloyloxymethyl)oxetane, 3-(methacryloyloxymethyl)-3-ethyl-oxetane, 3-(acryloyloxymethyl)-3-ethyl-oxetane, 3-(methacryloyloxymethyl)-2-trifluoromethyloxetane, 3-(acryloyloxymethyl)-2-trifluoromethyloxetane, 3-(methacryloyloxymethyl)-2-phenyl-oxetane, 3-(acryloyloxymethyl)-2-phenyl-oxetane, 2-(methacryloyloxymethyl)oxetane, 2-(acryloyloxymethyl)oxetane, 2-(methacryloyloxymethyl)-4-trifluoromethyloxetane, 2-(acryloyloxymethyl)-4-trifluoromethyloxetane are preferred, and 3-(methacryloyloxymethyl)-3-ethyl-oxetane, 3-(acryloyloxymethyl)-3-ethyl-oxetane, etc. are preferably used. Among these, from the viewpoint of adhesion to a substrate, X is preferably a carbonyloxy group or a methylene group, and Z is preferably an epoxy group.
[0031] In the present invention, when producing the copolymer of component (A), other monomers can be used together with the above monomers a, b, and c. Examples of such other monomers include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthryl methacrylate, anthryl methyl methacrylate, phenyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, γ-butyrolactone methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecyl methacrylate, 8-ethyl-8-tricyclodecyl methacrylate, methyl acrylate, ethyl acrylate, isopropyl acrylate, benzyl acrylate, naphthyl acrylate, anthryl acrylate, anthryl methyl acrylate, phenyl acrylate, cyclohexyl acrylate, isobornyl acrylate, methoxytriethylene glycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, γ-butyrolactone acrylate, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecyl acrylate, 8-ethyl-8-tricyclodecyl acrylate, styrene, vinyl naphthalene, vinyl anthracene, and vinyl biphenyl.
[0032] In the present invention, when the copolymer of component (A) is produced, the above-mentioned other monomers can be used to impart resistance to plating solutions and the like to the resulting copolymer of component (A).
[0033] The method for obtaining the specific copolymer used in the present invention is not particularly limited, but for example, the specific copolymer can be obtained by carrying out a polymerization reaction at a temperature of 50 to 110° C. in a solvent in which the above-mentioned monomer a, the above-mentioned monomer b, the above-mentioned monomer c, and optionally other monomers, polymerization initiators, etc. are coexistent. The solvent used in this case is not particularly limited as long as it dissolves the monomer having the specific functional group, the monomer not having the specific functional group that is used if desired, and the polymerization initiator, etc. Specific examples are described in <Solvent (C)> below. The specific copolymer obtained by the above method is usually in the state of a solution dissolved in a solvent.
[0034] In addition, the solution of the specific copolymer obtained by the above method can be poured into stirred diethyl ether or water to precipitate, and the resulting precipitate can be filtered and washed, and then dried at room temperature or by heating under normal or reduced pressure to obtain a powder of the specific copolymer. By the above operation, the polymerization initiator and unreacted monomers coexisting with the specific copolymer can be removed, and as a result, a powder of the purified specific copolymer can be obtained. If the specific copolymer cannot be sufficiently purified by one operation, the obtained powder can be redissolved in a solvent and the above operation can be repeated.
[0035] In the present invention, the specific copolymer may be used in the form of a powder, or in the form of a solution obtained by redissolving the purified powder in a solvent described below.
[0036] In the present invention, the specific copolymer of the component (A) may be a mixture of multiple specific copolymers.
[0037] In the present invention, the ratio of the monomer a and the monomer b to be copolymerized is preferably 0.05 to 5 moles, particularly preferably 0.1 to 3 moles, of the monomer a per mole of the monomer b, from the viewpoints of reactivity and plating property. In the present invention, the ratio of the monomer b and the monomer c to be copolymerized is preferably 0.05 to 3 moles, particularly preferably 0.1 to 1 mole, of the monomer c per mole of the monomer b, from the viewpoints of reactivity and plating property.
[0038] In the present invention, when the above-mentioned other monomers are used in producing the copolymer, which is the component (A), the amount of the other monomers is 1 to 200% by mole, more preferably 10 to 100% by mole, based on the total number of moles of the monomers a and b, or based on the total number of moles of the monomers a, b, and c.
[0039] <(B) Metal fine particles> The metal fine particles (B) used in the undercoat agent of the present invention are not particularly limited, and examples of the metal species include iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), tin (Sn), platinum (Pt), and gold (Au), as well as alloys thereof. These metals may be one type or two or more types of alloys. Among these, palladium fine particles are preferred as metal fine particles. The metal fine particles may be oxides of the above metals.
[0040] The metal fine particles can be obtained by reducing metal ions, for example, by irradiating a solution of a metal salt with light from a high-pressure mercury lamp, or by adding a compound having a reducing action (a so-called reducing agent) to the solution, etc. For example, a solution of a metal salt can be added to a solution in which the above-mentioned (A) component polymer is dissolved and irradiated with ultraviolet light, or a solution of a metal salt and a reducing agent can be added to the solution to reduce the metal ions, thereby forming a composite of the (A) component polymer and the metal fine particles, and a base agent containing the (A) component polymer and the metal fine particles can be prepared.
[0041] Examples of the metal salt include chloroauric acid, silver nitrate, copper sulfate, copper nitrate, copper acetate, tin chloride, platinous chloride, chloroplatinic acid, Pt(dba)2 [dba = dibenzylideneacetone], Pt(cod)2 [cod = 1,5-cyclooctadiene], Pt(CH3)2(cod), palladium chloride, palladium acetate (Pd(OC(=O)CH3)2), palladium nitrate, Pd2(dba)3·CHCl3, Pd(dba)2, rhodium chloride, rhodium acetate, ruthenium enka, ruthenium acetate, Ru(cod)(cot) [cot = cyclooctatriene], iridium chloride, iridium acetate, Ni(cod)2, and the like. The reducing agent is not particularly limited, and various reducing agents can be used, and it is preferable to select the reducing agent depending on the metal species to be contained in the obtained undercoat agent. Examples of the reducing agent that can be used include metal borohydrides such as sodium borohydride and potassium borohydride; aluminum hydride salts such as lithium aluminum hydride, potassium aluminum hydride, cesium aluminum hydride, beryllium aluminum hydride, magnesium aluminum hydride, and calcium aluminum hydride; hydrazine compounds; citric acid and its salts; succinic acid and its salts; ascorbic acid and its salts; primary or secondary alcohols such as methanol, ethanol, isopropanol, and polyols; trimethylamine, triethylamine, diisopropylethylamine, and diethylmethylamine. tertiary amines such as tetramethylethylenediamine [TMEDA] and ethylenediaminetetraacetic acid [EDTA]; hydroxylamine; and phosphines such as tri-n-propylphosphine, tri-n-butylphosphine, tricyclohexylphosphine, tribenzylphosphine, triphenylphosphine, triethoxyphosphine, 1,2-bis(diphenylphosphino)ethane [DPPE], 1,3-bis(diphenylphosphino)propane [DPPP], 1,1'-bis(diphenylphosphino)ferrocene [DPPF], and 2,2'-bis(diphenylphosphino)-1,1'-binaphthyl [BINAP].
[0042] The primary particle average particle size of the metal fine particles is preferably 1 to 100 nm. By setting the primary particle average particle size of the metal fine particles to 100 nm or less, the reduction in surface area is small and sufficient catalytic activity can be obtained. The primary particle average particle size is more preferably 75 nm or less, and particularly preferably 1 to 30 nm. The average particle size of primary particles can be measured by the following method. [Measurement of average particle size of primary particles] After dispersing metal particles in ethanol, the particles are dropped onto a carbon support film and dried to prepare a sample. The average primary particle size of the sample can then be determined by microscopy using a TEM device (Hitachi: H-8000, accelerating voltage 200 kV).
[0043] The amount of the copolymer (A) in the primer of the present invention is preferably 20 parts by mass or more and 10,000 parts by mass or less per 100 parts by mass of the metal fine particles (B). By making the amount of the copolymer (A) added to 100 parts by mass of the metal fine particles (B) 20 parts by mass or more, the metal fine particles can be sufficiently dispersed, and if it is 20 parts by mass or less, the dispersibility of the metal fine particles is insufficient, and precipitates and aggregates are likely to occur. More preferably, it is 30 parts by mass or more. Also, if the copolymer (A) is added in an amount of 10,000 parts by mass or more per 100 parts by mass of the metal fine particles (B), the amount of Pd per unit area after coating becomes insufficient, and the deposition property of the plating may be reduced.
[0044] <Base agent> The electroless plating primer of the present invention contains the copolymer (A), the metal fine particles (B), and the solvent (C), and further contains other components as necessary. In the electroless plating primer of the present invention, it is preferable that the copolymer (A) and the metal fine particles (B) form a complex, that is, it is preferable that the primer contains a complex formed by the copolymer (A) and the metal fine particles (B).
[0045] Here, the composite is a composite in which the two coexist in contact with or in close proximity to metal fine particles due to the action of the metal dispersing groups in the side chains of the copolymer, component (A), and form a particulate form; in other words, the composite is expressed as a composite having a structure in which metal fine particles are attached or coordinated to the metal dispersing groups of the copolymer, component (A). Here, the term "attached or coordinated structure" refers to a state in which some or all of the metal dispersing groups of the copolymer (A) interact with the metal particles, which is thought to form a complex-like structure. Therefore, when palladium particles are used as the metal particles, it is thought that the Pd atoms on the surface interact with the metal dispersing groups, forming a structure in which the polymer (A) surrounds the metal particles.
[0046] Therefore, the "composite" in the present invention may include not only a composite in which metal fine particles and the copolymer, component (A), are bonded to form a single composite as described above, but also a composite in which metal fine particles and the copolymer, component (A), exist independently of each other without forming a bond (appearing to form a single particle).
[0047] The formation of the composite of the copolymer (A) and the metal fine particles (B) is carried out simultaneously when preparing the undercoat agent containing the copolymer (A) and the metal fine particles, and the method thereof includes a method of synthesizing the metal fine particles stabilized to some extent by the metal dispersing group, and then exchanging the ligand with the polymer (A), or a method of forming the composite by directly reducing the metal ion in the solution of the copolymer (A). Also, as mentioned above, the composite can be formed by adding a solution of a metal salt to the solution in which the copolymer (A) is dissolved and irradiating it with ultraviolet light, or by adding a solution of a metal salt and a reducing agent to the solution, thereby reducing the metal ion.
[0048] In the direct reduction method, metal ions and the copolymer (A) are dissolved in a solvent and reduced with primary or secondary alcohols such as methanol, ethanol, 2-propanol, and polyols to obtain the desired metal microparticle composite. As the metal ion source used here, the above-mentioned metal salts can be used. The solvent used is not particularly limited as long as it is a solvent that can dissolve metal ions and a polymer having a metal-dispersing group at a required concentration or more. Specific examples of the solvent include alcohols such as methanol, ethanol, n-propanol, and 2-propanol; halogenated hydrocarbons such as methylene chloride and chloroform; cyclic ethers such as tetrahydrofuran (THF), 2-methyltetrahydrofuran, and tetrahydropyran; nitriles such as acetonitrile and butyronitrile; amides such as N,N-dimethylformamide (DMF) and N-methyl-2-pyrrolidone (NMP); sulfoxides such as dimethyl sulfoxide, and mixtures of these solvents. Preferred are alcohols, halogenated hydrocarbons, and cyclic ethers, and more preferred are ethanol, 2-propanol, chloroform, and tetrahydrofuran. The temperature for the reduction reaction (mixing the metal ions with the copolymer, which is component (A)) can usually be in the range of from 0°C to the boiling point of the solvent, and is preferably in the range of room temperature (about 25°C) to 100°C.
[0049] As another direct reduction method, the desired metal fine particle composite can be obtained by dissolving metal ions and the copolymer, which is component (A), in a solvent and reacting them in a hydrogen gas atmosphere. The metal ion source used here may be the above-mentioned metal salts or metal carbonyl complexes such as chromium hexacarbonyl [Cr(CO)6], iron pentacarbonyl [Fe(Co)5], dicobalt octacarbonyl [Co2(CO)8], nickel tetracarbonyl [Ni(CO)4], etc. Zero-valent metal complexes such as metal olefin complexes, metal phosphine complexes, and metal nitrogen complexes may also be used. The solvent used is not particularly limited as long as it is a solvent that can dissolve the metal ions and the copolymer, which is component (A), in a concentration greater than or equal to the required concentration. Specific examples of the solvent include alcohols such as ethanol and propanol; halogenated hydrocarbons such as methylene chloride and chloroform; cyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, and tetrahydropyran; nitriles such as acetonitrile and butyronitrile; and mixtures of these solvents, with tetrahydrofuran being preferred. The temperature at which the metal ions and the copolymer, component (A), are mixed is usually within the range of 0° C. to the boiling point of the solvent.
[0050] As a direct reduction method, the desired metal fine particle composite can be obtained by dissolving metal ions and the copolymer, which is component (A), in a solvent and subjecting them to a thermal decomposition reaction. The metal ion source used here may be the above-mentioned metal salts, metal carbonyl complexes, other zero-valent metal complexes, or metal oxides such as silver oxide. The solvent used is not particularly limited as long as it is a solvent that can dissolve the metal ions and the copolymer, which is component (A), in a concentration greater than or equal to the required concentration. Specific examples of the solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, and ethylene glycol; halogenated hydrocarbons such as methylene chloride and chloroform; cyclic ethers such as tetrahydrofuran (THF), 2-methyltetrahydrofuran, and tetrahydropyran; nitriles such as acetonitrile and butyronitrile; aromatic hydrocarbons such as benzene and toluene; and mixtures of these solvents, with toluene being preferred. The temperature at which the copolymer (A) containing metal ions and metal-dispersing groups is mixed can usually be in the range of 0°C to the boiling point of the solvent, and is preferably close to the boiling point of the solvent, for example 110°C (heated under reflux) in the case of toluene.
[0051] The composite of the copolymer and metal fine particles thus obtained as component (A) can be made into a solid form such as powder through a purification treatment such as reprecipitation.
[0052] The primer of the present invention contains the copolymer (A) as component, metal fine particles (B) (preferably a composite thereof), and a solvent (C), and further contains other components as necessary. The primer may be in the form of a varnish used when forming the [primer layer for electroless metal plating] described below.
[0053] The electroless plating primer of the present invention may contain a base resin as component (D) if desired. Component (D) is preferably one having a non-radically polymerizable crosslinking group that undergoes a crosslinking reaction with the crosslinking group in component (A) by heat, and is preferably, for example, one described as component (B) in WO2014 / 171376. By adding such component (D), other functions (e.g., adhesion, heat resistance, photosensitivity, dielectric properties, etc.) of the resulting undercoat layer may be further improved.
[0054] When the plating undercoat agent of the present invention contains the component (D), the content is preferably 0 to 200 parts by mass, more preferably 0 to 150 parts by mass, based on 100 parts by mass of the total of the copolymer (A) and the metal fine particles (B). If the content of the component (D) is too high, the plating deposition property may decrease.
[0055] The electroless plating primer of the present invention may contain a crosslinking agent, which is the component (E), if desired.
[0056] Examples of the crosslinking agent which is component (E) include compounds such as epoxy compounds, methylol compounds, blocked isocyanate compounds, phenoplast compounds, compounds having two or more trialkoxysilyl groups, alkoxysilane compounds having an amino group, organometallic compounds having an alkoxy group and / or a chelating ligand, polymers of N-alkoxymethylacrylamide, polymers of compounds having an epoxy group, polymers of compounds having an alkoxysilyl group, polymers of compounds having an isocyanate group, and polymers such as melamine formaldehyde resins.
[0057] Specific examples of the epoxy compounds include ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane.
[0058] Specific examples of the above-mentioned methylol compound include compounds such as alkoxymethylated glycoluril, alkoxymethylated benzoguanamine, and alkoxymethylated melamine.
[0059] Specific examples of alkoxymethylated glycolurils include 1,3,4,6-tetrakis(methoxymethyl)glycoluril, 1,3,4,6-tetrakis(butoxymethyl)glycoluril, 1,3,4,6-tetrakis(hydroxymethyl)glycoluril, 1,3-bis(hydroxymethyl)urea, 1,1,3,3-tetrakis(butoxymethyl)urea, 1,1,3,3-tetrakis(methoxymethyl)urea, 1,3-bis(hydroxymethyl)-4,5-dihydroxy-2-imidazolinone, and 1,3-bis(methoxymethyl)-4,5-dimethoxy-2-imidazolinone. Commercially available products include glycoluril compounds manufactured by Mitsui Cytec Co., Ltd. (product names: Cymel (registered trademark) 1170, Powderlink (registered trademark) 1174), methylated urea resins (product names: UFR (registered trademark) 65), butylated urea resins (product names: UFR (registered trademark) 300, U-VAN10S60, U-VAN10R, U-VAN11HV), and urea / formaldehyde resins (high condensation type, product names: Beckamin (registered trademark) J-300S, P-955, and N) manufactured by DIC Corporation.
[0060] Specific examples of alkoxymethylated benzoguanamine include tetramethoxymethylbenzoguanamine, etc. Commercially available products include those manufactured by Mitsui Cytec Co., Ltd. (product name: Cymel (registered trademark) 1123) and those manufactured by Sanwa Chemical Co., Ltd. (product names: Nikalac (registered trademark) BX-4000, BX-37, BL-60, and BX-55H).
[0061] Specific examples of alkoxymethylated melamine include hexamethoxymethylmelamine, etc. Commercially available products include methoxymethyl type melamine compounds (trade names: Cymel (registered trademark) 300, 301, 303, 350) manufactured by Mitsui Cytec Co., Ltd., butoxymethyl type melamine compounds (trade names: Mycoat (registered trademark) 506, 508) manufactured by Sanwa Chemical Co., Ltd., methoxymethyl type melamine compounds (trade names: Nikalac (registered trademark) MW-30, MW-22, MW-11, MS-001, MX-002, MX-730, MX-750, MX-035) manufactured by Sanwa Chemical Co., Ltd., and butoxymethyl type melamine compounds (trade names: Nikalac (registered trademark) MX-45, MX-410, MX-302) manufactured by Sanwa Chemical Co., Ltd.
[0062] Also, it may be a compound obtained by condensing a melamine compound, a urea compound, a glycoluril compound, and a benzoguanamine compound in which the hydrogen atom of the amino group is substituted with a methylol group or an alkoxymethyl group. For example, a high molecular weight compound produced from a melamine compound and a benzoguanamine compound described in U.S. Patent No. 6,323,310 may be mentioned. An example of a commercially available product of the melamine compound is a product name: Cymel (registered trademark) 303 (manufactured by Mitsui Cytec Co., Ltd.), and an example of a commercially available product of the benzoguanamine compound is a product name: Cymel (registered trademark) 1123 (manufactured by Mitsui Cytec Co., Ltd.).
[0063] The above-mentioned blocked isocyanate compound has two or more isocyanate groups in one molecule, each of which is blocked with an appropriate protecting group. When exposed to high temperatures during thermal curing, the protecting groups (blocking moieties) are thermally dissociated and removed, and the resulting isocyanate groups undergo a crosslinking reaction with the resin.
[0064] Such a polyfunctional blocked isocyanate compound can be obtained, for example, by reacting a polyfunctional isocyanate compound having two or more isocyanate groups in one molecule with a suitable blocking agent.
[0065] Examples of the polyfunctional isocyanate compound include 1,4-tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 1,3,6-hexamethylene triisocyanate, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,3-bis( Isocyanatemethyl)cyclohexane, 1,4-cyclohexyl diisocyanate, 2,6-bis(isocyanatomethyl)tetrahydrodicyclopentadiene, bis(isocyanatomethyl)dicyclopentadiene, bis(isocyanatomethyl)adamantane, 2,5-diisocyanatomethylnorbornene, norbornane diisocyanate, dicycloheptane triisocyanate, 4,4'-diphenylmethane diisocyanate, 2 ,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, 1,3-bis(isocyanatemethyl)benzene, dianisidine diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, diphenyl ether diisocyanate, 2,6-bis(isocyane (trimethyl)decahydronaphthalene, bis(diisocyanatolyl)phenylmethane, 1,1'-methylenebis(3-methyl-4-isocyanatobenzene), 1,3-bis(1-isocyanato-1-methylethyl)benzene, 1,4-bis(1-isocyanato-1-methylethyl)benzene, 4,4'-biphenylene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,Examples of the compound include 4'-biphenylene diisocyanate, bis(isocyanate methyl)thiophene, bis(isocyanate methyl)tetrahydrothiophene, and modified compounds thereof (for example, isocyanurate, biuret, ethylene glycol adduct, propylene glycol adduct, trimethylolpropane adduct, ethanolamine adduct, polyester polyol adduct, polyether polyol adduct, polyamide adduct, and polyamine adduct).
[0066] Examples of the blocking agent include methanol, ethanol, isopropanol, n-butanol, heptanol, hexanol, 2-ethoxyhexanol, cyclohexanol, octanol, isononyl alcohol, stearyl alcohol, benzyl alcohol, 2-ethoxyethanol, methyl lactate, ethyl lactate, amyl lactate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol monoethyl ether, N,N-dimethylaminoethanol, N,N-diethylaminoethanol, N,N-dimethyl ... Alcohols such as butylaminoethanol, phenol, ethylphenol, propylphenol, butylphenol, octylphenol, nonylphenol, nitrophenol, chlorophenol, o-cresol, m-cresol, p-cresol, xylenol, and other phenols, lactams such as α-pyrrolidone, β-butyrolactam, β-propiolactam, γ-butyrolactam, δ-valerolactam, and ε-caprolactam, acetone oxime, methyl ethyl ketone oxime, methyl isobutyl ketone oxime, diethyl ketone oxime, cyclohexanone oxime, acetophenone oxime, and benzophenone oxime, and other oximes, pyrazole, 3,5-dimethylpyrazole, 3-methylpyrazole, 4-benzyl-3,5-dimethylpyrazole, 4-nitro-3,5-dimethylpyrazole, 4-bromo-3,Pyrazoles such as 5-dimethylpyrazole and 3-methyl-5-phenylpyrazole; mercaptans such as butyl mercaptan, hexyl mercaptan, dodecyl mercaptan, and benzenethiol; active methylene compounds such as malonic acid diesters, acetoacetic acid esters, malonic acid dinitrile, acetylacetone, methylene disulfone, dibenzoylmethane, dipivaloylmethane, and acetone dicarboxylate diester; dibutylamine, diisopropylamine, di-tert-butylamine, and di(2-ethylhexyl)amine. Examples of the compound include amines such as (xyl)amine, dicyclohexylamine, benzylamine, diphenylamine, aniline, and carbazole, imidazoles such as imidazole and 2-ethylimidazole, imines such as methyleneimine, ethyleneimine, polyethyleneimine, and propyleneimine, acid amides such as acetanilide, acrylamide, acetate amide, and dimer acid amide, acid imides such as succinimide, maleimide, and phthalimide, and urea compounds such as urea, thiourea, and ethyleneurea. The compound may also be an internal block type formed by a uretdione bond (dimerization of an isocyanate group).
[0067] Examples of commercially available polyfunctional blocked isocyanate compounds include the following products. Takenate (registered trademark) B-815N, B-830, B-842N, B-846N, B-870, B-870N, B-874, B-874N, B-882, B-882N, B-5010, B-7005, B-7030, and B-7075 (all manufactured by Mitsui Chemicals, Inc.).
[0068] Duranate (registered trademark) ME20-B80S, MF-B60B, MF-B60X, MF-B90B, MF-K60B, MF-K60X, SBN-70D, 17B-60P, 17B-60PX, TPA-B80E, TPA-B80X, E402-B80B, E402-B80T, K6000 (all manufactured by Asahi Kasei Chemicals Corporation), Coronate (registered trademark) 2503, 2507, 2512, 2513, 2515, 2520, 2554, BI-301, AP-M, Millionate MS-50 (all manufactured by Tosoh Corporation).
[0069] Burnock (registered trademark) D-500, D-550, and DB-980K (all manufactured by DIC Corporation).
[0070] Sumidur (registered trademark) BL-3175, BL-4165, BL-4265, BL-1100, BL-1265, Desmodur (registered trademark) TPLS-2957, TPLS-2062, TPLS-2078, TPLS-2117, BL-3475, Desmotherm (registered trademark) 2170, 2265 (all manufactured by Sumika Bayer Urethane Co., Ltd.).
[0071] TRIXENE BI-7641, BI-7642, BI-7986, BI-7987, BI-7950, BI-7951, BI-7960, BI-7961, BI-7963, BI-7981, BI-7982, BI-7984, BI-7986, BI-7990, BI-7991, BI-7992, BI-7770, BI-7772, BI-7779, DP9C / 214 (all manufactured by Baxten Chemicals).
[0072] VESTANAT (registered trademark) B1358A, B1358 / 100, B1370, VESTAGON (registered trademark) B1065, B1400, B1530, BF1320, BF1540 (all manufactured by Evonik Industries).
[0073] The polyfunctional blocked isocyanate compound may be a homopolymer or copolymer obtained by radical polymerization of a (meth)acrylate having a blocked isocyanate group. Here, the copolymer means a polymer obtained by polymerizing two or more monomers. The copolymer may be a copolymer obtained by polymerizing two or more (meth)acrylates having a blocked isocyanate group, or a copolymer obtained by polymerizing a (meth)acrylate having a blocked isocyanate group and another (meth)acrylate. Examples of commercially available products of such a (meth)acrylate having a blocked isocyanate group include Karenz (registered trademark) MOI-BM, AOI-BM, MOI-BP, AOI-BP, MOI-DEM, MOI-CP, MOI-MP, MOI-OEt, MOI-OBu, and MOI-OiPr manufactured by Showa Denko K.K.
[0074] These polyfunctional blocked isocyanate compounds may be used alone or in combination of two or more kinds.
[0075] Specific examples of the above-mentioned phenoplast compound include the following compounds, but the phenoplast compound is not limited to the following compound examples.
[0076] [ka]
[0077] Specific examples of compounds having two or more trialkoxysilyl groups include 1,4-bis(trimethoxysilyl)benzene, 1,4-bis(triethoxysilyl)benzene, 4,4'-bis(trimethoxysilyl)biphenyl, 4,4'-bis(triethoxysilyl)biphenyl, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)ethane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(trimethoxysilyl)ethylene, bis(triethoxysilyl)ethylene, 1,3-bis(trimethoxysilylethyl)tetramethyldisiloxane, 1,3-bis(triethoxysilylethyl)tetramethyldisiloxane, bis(triethoxysilylmethyl)amine, bis(trimethoxysilylmethyl)amine, bis(triethoxysilylpropyl)amine, bis(trimethoxysilylpropyl)amine, and bis(3-trimethoxysilylpropyl)carbonate. ester, bis(3-triethoxysilylpropyl)carbonate, bis[(3-trimethoxysilyl)propyl]disulfide, bis[(3-triethoxysilyl)propyl]disulfide, bis[(3-trimethoxysilyl)propyl]thiourea, bis[(3-triethoxysilyl)propyl]thiourea, bis[(3-trimethoxysilyl)propyl]urea, bis[(3-triethoxysilyl)propyl]urea, 1,4-bis(trimethoxysilyl)propyl Examples of compounds include 1,4-bis(triethoxysilylmethyl)benzene, 1,4-bis(triethoxysilylmethyl)benzene, tris(trimethoxysilylpropyl)amine, tris(triethoxysilylpropyl)amine, 1,1,2-tris(trimethoxysilyl)ethane, 1,1,2-tris(triethoxysilyl)ethane, tris(3-trimethoxysilylpropyl)isocyanurate, and tris(3-triethoxysilylpropyl)isocyanurate.
[0078] Specific examples of alkoxysilane compounds having an amino group include N,N'-bis[3-(trimethoxysilyl)propyl]-1,2-ethanediamine, N,N'-bis[3-(triethoxysilyl)propyl]-1,2-ethanediamine, N-[3-(trimethoxysilyl)propyl]-1,2-ethanediamine, N-[3-(triethoxysilyl)propyl]-1,2-ethanediamine, bis-{3-(trimethoxysilyl)propyl}amine, and bis-{3-(triethoxysilyl)propyl}amine. , 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, trimethoxy{3-(methylamino)propylsilane, 3-(N-allylamino)propyltrimethoxysilane, 3-(N-allylamino)propyltriethoxysilane, 3-(diethylamino)propyltrimethoxysilane, 3-(diethylamino)propyltriethoxysilane, 3-(phenylamino)propyltrimethoxysilane, and 3-(phenylamino)propyltriethoxysilane.
[0079] Specific examples of organometallic compounds having an alkoxy group and / or a chelating ligand include compounds such as diisopropoxyethyl acetoacetate aluminum, diisopropoxy acetylacetonate aluminum, triacetylacetonate aluminum, tetrakisisopropoxytitanium, tetrakisnormalbutoxytitanium, tetraoctyl titanate, diisopropoxybis(acetylacetonate)titanium, titanium tetraacetylacetonate, tetrakis(normalpropoxy)zirconium, tetrakis(normalbutoxy)zirconium, and tetrakis(acetylacetonate)zirconium.
[0080] Furthermore, examples of the above-mentioned N-alkoxymethylacrylamide polymers include polymers produced using acrylamide compounds or methacrylamide compounds substituted with a hydroxymethyl group or an alkoxymethyl group, such as N-hydroxymethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, and N-butoxymethyl(meth)acrylamide.
[0081] Specific examples of such polymers include poly(N-butoxymethylacrylamide), a copolymer of N-butoxymethylacrylamide and styrene, a copolymer of N-hydroxymethylmethacrylamide and methyl methacrylate, a copolymer of N-ethoxymethylmethacrylamide and benzyl methacrylate, and a copolymer of N-butoxymethylacrylamide, benzyl methacrylate, and 2-hydroxypropyl methacrylate, etc. The weight-average molecular weight of such polymers is 1,000 to 200,000, more preferably 3,000 to 150,000, and even more preferably 3,000 to 50,000.
[0082] Examples of the polymer of a compound having an epoxy group include polymers produced using a compound having an epoxy group, such as glycidyl methacrylate, 3,4-epoxycyclohexylmethyl methacrylate, and 3,4-epoxycyclohexylmethyl methacrylate.
[0083] Specific examples of such polymers include poly(3,4-epoxycyclohexylmethyl methacrylate), poly(glycidyl methacrylate), a copolymer of glycidyl methacrylate and methyl methacrylate, a copolymer of 3,4-epoxycyclohexylmethyl methacrylate and methyl methacrylate, a copolymer of glycidyl methacrylate and styrene, etc. The weight average molecular weight of such polymers is 1,000 to 200,000, more preferably 3,000 to 150,000, and further preferably 3,000 to 50,000.
[0084] Examples of the polymer of the compound having an alkoxysilyl group include polymers produced by using a compound having an alkoxysilyl group, such as 3-methacryloxypropyltrimethoxysilane.
[0085] Specific examples of such polymers include poly(3-methacryloxypropyltrimethoxysilane), a copolymer of 3-methacryloxypropyltrimethoxysilane and styrene, and a copolymer of 3-methacryloxypropyltrimethoxysilane and methyl methacrylate. The weight-average molecular weight of such polymers is 1,000 to 200,000, more preferably 3,000 to 150,000, and even more preferably 3,000 to 50,000. In this specification, the above-mentioned "poly((meth)acryloxypropyltrimethoxysilane)" means a poly(meth)acrylate having an alkoxysilyl group.
[0086] These crosslinking agents can be used alone or in combination of two or more kinds.
[0087] When the plating primer of the present invention contains the (E) component, the content thereof is preferably 0 to 100 parts by mass, and more preferably 0 to 50 parts by mass, based on a total of 100 parts by mass of the copolymer of the (A) component and the metal fine particles of the (B) component.
[0088] <Other additives> The base agent of the present invention may further contain additives such as surfactants, various surface conditioners, thickeners, etc., as appropriate, so long as the effects of the present invention are not impaired.
[0089] Examples of the above surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene-polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan tristearate, and sorbitan trioleate; polyoxyethylene sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan tristearate, and sorbitan trioleate; Examples of suitable surfactants include polyoxyethylene nonionic surfactants such as polyoxyethylene sorbitan urate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, and polyoxyethylene sorbitan trioleate; and fluorosurfactants such as F-TOP (registered trademark) EF-301, EF-303, and EF-352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Megafac (registered trademark) F-171, F-173, R-08, and R-30 (all manufactured by DIC Corporation), Novec (registered trademark) FC-430 and FC-431 (all manufactured by Sumitomo 3M Limited), Asahiguard (registered trademark) AG-710 (manufactured by Asahi Glass Co., Ltd.), and Surflon (registered trademark) S-382 (manufactured by AGC Seimi Chemical Co., Ltd.).
[0090] Examples of the surface conditioner include silicone-based leveling agents such as Shin-Etsu Silicone (registered trademark) KP-341 [manufactured by Shin-Etsu Chemical Co., Ltd.]; and silicone-based surface conditioners such as BYK (registered trademark)-302, 307, 322, 323, 330, 333, 370, 375, and 378 [all manufactured by BYK Japan K.K.].
[0091] Examples of the thickener include polyacrylic acids (including crosslinked ones) such as carboxyvinyl polymer (carbomer); vinyl polymers such as polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polyvinyl acetate (PVAc), and polystyrene (PS); polyethylene oxides; polyesters; polycarbonates; polyamides; polyurethanes; polysaccharides such as dextrin, agar, carrageenan, alginic acid, gum arabic, guar gum, tragacanth gum, locust bean gum, starch, pectin, carboxymethylcellulose, hydroxyethylcellulose, and hydroxypropylcellulose; and proteins such as gelatin and casein. The above-mentioned polymers include not only homopolymers but also copolymers. These thickeners may be used alone or in combination of two or more. The viscosity and rheological properties of the primer of the present invention can be adjusted by blending a thickener as necessary, and the viscosity and rheological properties of the primer can be appropriately selected and adopted depending on the application, such as the application method and application location of the primer.
[0092] These additives may be used alone or in combination of two or more. The amount of the additive used is preferably 0.001 to 50 parts by mass, more preferably 0.005 to 10 parts by mass, and even more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the composite formed from the polymer (A) component and the metal fine particles (B) component.
[0093] [Undercoat layer for electroless metal plating] The above-mentioned electroless plating primer of the present invention can be applied to a substrate to form an underlayer for electroless metal plating. This underlayer for electroless metal plating is also within the scope of the present invention.
[0094] The substrate is not particularly limited, but a non-conductive substrate or a conductive substrate can be preferably used. Examples of non-conductive substrates include glass, ceramics, polyethylene resin, polypropylene resin, vinyl chloride resin, nylon (polyamide resin), polyimide resin, polycarbonate resin, acrylic resin, PEN (polyethylene naphthalate) resin, PET (polyethylene terephthalate) resin, PEEK (polyether ether ketone) resin, ABS (acrylonitrile-butadiene-styrene copolymer) resin, epoxy resin, polyacetal resin, LCP (liquid crystal polymer) resin, paper, etc. These are preferably used in the form of a sheet or film, etc., and in this case, the thickness is not particularly limited. Examples of the conductive base material include ITO (tin-doped indium oxide), ATO (antimony-doped tin oxide), FTO (fluorine-doped tin oxide), AZO (aluminum-doped zinc oxide), GZO (gallium-doped zinc oxide), as well as metals such as various stainless steels, aluminum and aluminum alloys such as duralumin, iron and iron alloys, copper and copper alloys such as brass, phosphor bronze, cupro-nickel and beryllium copper, nickel and nickel alloys, and silver and silver alloys such as nickel silver. Furthermore, a substrate in which a thin film of these conductive materials is formed on the above-mentioned non-conductive substrate can also be used. The substrate may be a three-dimensional molded body.
[0095] A specific method for forming an underlayer for electroless metal plating from an electroless plating undercoat agent containing the above-mentioned (A) component copolymer, (B) metal fine particles (preferably a composite thereof), and (C) solvent, and further containing (D) base resin, (E) crosslinking agent, and other components as required, is to first dissolve or disperse the above-mentioned (A) component polymer and (B) metal fine particles (preferably a composite thereof) (and (D) base resin, (E) crosslinking agent, and other components as required) in the (C) solvent to form a varnish, and then apply the varnish to a substrate on which a metal plating film is to be formed by a method such as spin coating, blade coating, dip coating, roll coating, bar coating, or the like. A thin layer is formed by applying the coating material using a method such as die coating, spray coating, inkjet printing, pen lithography such as fountain pen nanolithography (FPN) and dip pen nanolithography (DPN), letterpress printing, flexography, resin relief printing, contact printing, microcontact printing (μCP), nanoimprinting lithography (NIL), nanotransfer printing (nTP), and other relief printing methods, gravure printing, engraving, and other intaglio printing methods, lithography printing, screen printing, mimeograph printing, and other stencil printing methods, and offset printing, and then evaporating and drying the solvent. Among these coating methods, bar coating, flexographic printing, gravure printing, spin coating, spray coating, inkjet, pen lithography, contact printing, μCP, NIL and nTP are preferred. When using spin coating, it is possible to apply in a short time, so even a highly volatile solution can be used, and it is advantageous in that highly uniform coating can be performed. When using spray coating, highly uniform coating can be performed with a very small amount of varnish, which is very advantageous industrially. When using inkjet, pen lithography, contact printing, μCP, NIL, nTP, for example, fine patterns such as wiring can be efficiently formed (drawn), which is very advantageous industrially.
[0096] <(C) Solvent> The solvent used here is not particularly limited as long as it dissolves or disperses the polymer (A) component and the metal fine particles (B) (preferably a composite thereof), and, if desired, the components (D) and (E) and other components. Examples of the solvent include water; aromatic hydrocarbons such as benzene, toluene, xylene, ethylbenzene, chlorobenzene, and dichlorobenzene; alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, n-hexanol, n-octanol, 2-octanol, and 2-ethylhexanol; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and phenyl cellosolve; propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, dipropylene glycol monomethyl ether, triethylene glycol monomethyl ether, tripropylene glycol monomethyl ether, ethylene glycol dimethyl ether, and the like. glycol ethers such as ethylene glycol monomethyl ether acetate and propylene glycol monomethyl ether acetate (PGMEA); ethers such as tetrahydrofuran (THF), methyltetrahydrofuran, 1,4-dioxane and diethyl ether; esters such as ethyl acetate and butyl acetate; ketones such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone and cyclohexanone; aliphatic hydrocarbons such as n-heptane, n-hexane and cyclohexane; halogenated aliphatic hydrocarbons such as 1,2-dichloroethane and chloroform;Amides such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide; dimethyl sulfoxide, etc., can be used. These solvents may be used alone or in combination of two or more. Furthermore, glycols such as ethylene glycol, propylene glycol, and butylene glycol may be added to adjust the viscosity of the varnish. The concentration of the non-solvent components dissolved or dispersed in the above-mentioned solvent is arbitrary, but the concentration of the non-solvent components in the varnish [the concentration of all components excluding the solvent contained in the primer (the concentration of the polymer (A) and metal fine particles (B) (preferably a composite thereof), and optionally the base polymer (D), the crosslinking agent (E) and other components, etc.)] is 0.05 to 90 mass%, and preferably 0.1 to 80 mass%.
[0097] The method of drying the solvent is not particularly limited, and for example, the solvent may be evaporated using a hot plate or oven under a suitable atmosphere, i.e., in air, inert gas such as nitrogen, or in vacuum. This makes it possible to obtain an undercoat layer having a uniform film formation surface. The baking temperature is not particularly limited as long as the solvent can be evaporated, but it is preferable to perform the baking at 40 to 250°C.
[0098] [Electroless plating, metal plating film, metal-coated substrate] The electroless metal plating underlayer formed on the substrate thus obtained is electrolessly plated to form a metal plating film on the underlayer. The metal plating film thus obtained, as well as a metal-coated substrate having an electroless metal plating underlayer and a metal plating film on the substrate in this order, are also objects of the present invention. The electroless plating process (step) is not particularly limited and may be any commonly known electroless plating process. For example, a commonly used method involves using a conventionally known electroless plating solution and immersing an electroless metal plating underlayer formed on a substrate in the plating solution (bath).
[0099] The electroless plating solution mainly contains metal ions (metal salts), a complexing agent, and a reducing agent, and also contains other additives such as a pH adjuster, a pH buffer, a reaction accelerator (a second complexing agent), a stabilizer, and a surfactant (for imparting gloss to the plating film, improving the wettability of the treated surface, etc.) according to the intended use. Metals used in the metal plating film formed by electroless plating include iron, cobalt, nickel, copper, palladium, silver, tin, platinum, gold and alloys thereof, and are appropriately selected depending on the purpose. The complexing agent and reducing agent may also be appropriately selected depending on the metal ion.
[0100] In addition, the electroless plating solution may be a commercially available plating solution, for example, electroless nickel plating chemicals (Melplate (registered trademark) NI series) and electroless copper plating chemicals (Melplate (registered trademark) CU series) manufactured by Meltex Co., Ltd.; electroless nickel plating solution (ICP Nicoron (registered trademark) series, Top Piena 650) manufactured by Okuno Chemical Industries Co., Ltd., electroless copper plating solution (OPC-700 electroless copper MK, ATS Add Copper IW, ATS CT, OPC Copper (registered trademark) AF series, HFS, ATS NCA), electroless tin plating solution (Substar SN-5), electroless gold plating solution (Flash Gold 330, Self Gold OTK-IT), electroless silver plating solution (Muden Silver) manufactured by Kojima Chemical Co., Ltd., electroless palladium plating solution (Palette II) and electroless gold plating solution (Dip G series, NC Gold series) manufactured by Sasaki Chemical Co., Ltd.; electroless silver plating solution (S-Diamond AG-40) manufactured by Nippon Kanigen Co., Ltd. and electroless nickel plating solutions (Kanigen (registered trademark) series, Schumer (registered trademark) series, Schumer (registered trademark) Kaniblack (registered trademark) series) and electroless palladium plating solutions (S-KPD) manufactured by Dow Chemical; electroless copper plating solutions (Cuposit (registered trademark) Coppermix series, Circuposit (registered trademark) series), electroless palladium plating solutions (Paramers (registered trademark) series), electroless nickel plating solutions (Duraposit (registered trademark) series), electroless gold plating solutions (Aurolectroless (registered trademark) series), and electroless tin plating solutions (Tinposit (registered trademark) series) manufactured by The Dow Chemical Company; electroless copper plating solutions (Sulcup (registered trademark) ELC-SP, PSY, PCY, PGT, PSR, PEA, PMK) manufactured by Uemura Kogyo Co., Ltd., and electroless copper plating solutions (Printganth (registered trademark) PV, PVE) manufactured by Atotech Japan K.K. can be suitably used.
[0101] In the above electroless plating process, the formation rate and thickness of the metal coating can be controlled by adjusting the temperature, pH, immersion time, metal ion concentration, presence or absence of stirring and the stirring speed, presence or absence of air / oxygen supply and the supply speed, etc. of the plating bath. EXAMPLES
[0102] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The number average molecular weight and weight average molecular weight were measured as follows. [Measurement of number average molecular weight and weight average molecular weight] The number average molecular weight and weight average molecular weight of the copolymers obtained according to the following synthesis examples were measured using a GPC apparatus (Shodex column KD800 and TOSOH column TSK-GEL) manufactured by Tosoh Corporation under the condition that the elution solvent N,N-dimethylformamide (containing 10 mmol / L (liter) of lithium bromide hydrate (LiBr·H2O) as an additive) was passed through the column at a flow rate of 1 mL / min (column temperature 40°C) to elute. The following number average molecular weight (hereinafter referred to as Mn) and weight average molecular weight (hereinafter referred to as Mw) are expressed in terms of polystyrene.
[0103] The abbreviations used in the following examples have the following meanings. HEA: 2-hydroxyethyl acrylate NVA: N-vinylacetamide GMA: glycidyl methacrylate Cyclomer M100: 3,4-epoxycyclohexylmethyl methacrylate (manufactured by Daicel) Viscoat 3F: 2,2,2-trifluoroethyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) HFIP-M: Hexafluoro-2-propyl methacrylate (manufactured by Central Glass) FAMAC-6: 2-(perfluorohexyl)ethyl methacrylate (manufactured by Unimatec) AMBN: 2,2'-azobis-2-methylbutyronitrile PGME: Propylene glycol monomethyl ether IPE: Diisopropyl ether BL-10: Polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd.) 8KX-127: Acrylic resin (manufactured by Taisei Fine Chemical Co., Ltd.) [Polymer synthesis]
[0104] <Synthesis Example 1> 2.00g of styrene, 1.63g of NVA, 2.23g of HEA, and 0.29g of AMBN were dissolved in 14.37g of PGME and reacted at 80°C for 20 hours to obtain common The polymer solution (solid concentration 30% by mass) was poured into 500 mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and vacuum dried at 50°C to obtain a copolymer powder (P1). The obtained polymer had an Mn of 6,806 and an Mw of 11,797.
[0105] <Synthesis Example 2> 2.00g of styrene, 1.63g of NVA, 2.73g of GMA, and 0.32g of AMBN were dissolved in 15.59g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P2). The Mn and Mw of the resulting copolymer were 6,057 and 8,884, respectively.
[0106] <Synthesis Example 3> 2.00g of styrene, 1.63g of NVA, 3.76g of Cyclomer M100, and 0.37g of AMBN were dissolved in 18.14g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P3). The Mn of the resulting copolymer was 5,336 and the Mw was 8,669.
[0107] <Synthesis Example 4> 2.00g of styrene, 1.63g of NVA, 1.56g of HEA, 0.89g of Viscoat 3F, and 0.30g of AMBN were dissolved in 14.90g of PGME, and the copolymer solution (solid concentration 30% by mass) obtained by reacting at 80°C for 20 hours was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P4). The Mn of the obtained copolymer was 7,669 and the Mw was 16,610.
[0108] <Synthesis Example 5> 2.00g of styrene, 1.63g of NVA, 1.56g of HEA, 2.49g of FAMAC-6, and 0.38g of AMBN were dissolved in 18.83g of PGME, and the copolymer solution (solid concentration 30% by mass) obtained by reacting at 80°C for 20 hours was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P5). The Mn of the obtained copolymer was 6,146 and the Mw was 13,143.
[0109] <Synthesis Example 6> Styrene 2.00g, NVA 1.63g, GMA 1.91g, Viscoat 3F 0.89g, AMBN 0.32g were dissolved in PGME 15.76g, and the copolymer solution (solid concentration 30 mass%) obtained by reacting at 80 ° C for 20 hours was poured into diethyl ether 500mL while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and vacuum dried at 50 ° C to obtain a copolymer powder (P6). The Mn of the obtained copolymer was 6,170 and Mw was 10,023.
[0110] <Synthesis Example 7> 2.00g of styrene, 1.63g of NVA, 1.91g of GMA, 1.36g of HFIP-M, and 0.34g of AMBN were dissolved in 16.92g of PGME, and the copolymer solution (solid concentration 30% by mass) obtained by reacting at 80°C for 20 hours was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P7). The Mn of the obtained copolymer was 5,257 and the Mw was 9,324.
[0111] <Synthesis Example 8> 2.00g of styrene, 1.63g of NVA, 1.91g of GMA, 2.49g of FAMAC-6, and 0.40g of AMBN were dissolved in 19.69g of PGME, and the copolymer solution (solid concentration 30% by mass) obtained by reacting at 80°C for 20 hours was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P8). The Mn of the obtained copolymer was 4,718 and the Mw was 8,940.
[0112] <Synthesis Example 9> 2.00g of styrene, 1.63g of NVA, 2.64g of Cyclomer M100, 0.89g of Viscoat 3F, and 0.36g of AMBN were dissolved in 17.54g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P9). The Mn of the resulting copolymer was 6,558 and the Mw was 10,706.
[0113] <Synthesis Example 10> 2.00g of styrene, 1.63g of NVA, 2.64g of Cyclomer M100, 1.36g of HFIP-M, and 0.38g of AMBN were dissolved in 18.70g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P10). The Mn of the resulting copolymer was 5,021 and the Mw was 8,277.
[0114] <Synthesis Example 11> 2.00g of styrene, 1.63g of NVA, 2.64g of Cyclomer M100, 2.49g of FAMAC-6, and 0.44g of AMBN were dissolved in 21.47g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P11). The Mn of the resulting copolymer was 4,842 and the Mw was 7,853.
[0115] <Synthesis Example 12> 2.00g of styrene, 1.63g of NVA, 1.88g of Cyclomer M100, 1.48g of Viscoat 3F, and 0.35g of AMBN were dissolved in 17.14g of PGME, and the copolymer solution (solid concentration 30% by mass) obtained by reacting at 80°C for 20 hours was poured into 500mL of diethyl ether while stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P12). The Mn of the obtained copolymer was 6,592 and the Mw was 10,717.
[0116] <Synthesis Example 13> 2.00g of styrene, 1.63g of NVA, 1.88g of Cyclomer M100, 4.15g of FAMAC-6, and 0.48g of AMBN were dissolved in 23.69g of PGME, and the resulting copolymer solution (solid concentration 30% by mass) was reacted at 80°C for 20 hours. The resulting copolymer was poured into 500mL of diethyl ether with stirring to precipitate the polymer. The precipitated polymer was filtered under reduced pressure and dried in vacuum at 50°C to obtain a copolymer powder (P13). The Mn of the resulting copolymer was 5,814 and the Mw was 8,518.
[0117] [Synthesis of Pd particle composite] <Synthesis Example 14> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution in which 1.0 g of P1 polymerized in Synthesis Example 1 was dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M1) as a black powder.
[0118] <Synthesis Example 15> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P2 polymerized in Synthesis Example 2 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) with stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M2) as a black powder.
[0119] <Synthesis Example 16> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P3 polymerized in Synthesis Example 3 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M3) as a black powder.
[0120] <Synthesis Example 17> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P4 polymerized in Synthesis Example 4 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M4) as a black powder.
[0121] <Synthesis Example 18> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P5 polymerized in Synthesis Example 5 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M5) as a black powder.
[0122] <Synthesis Example 19> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P6 polymerized in Synthesis Example 6 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M6) as a black powder.
[0123] <Synthesis Example 20> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P7 polymerized in Synthesis Example 7 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M7) as a black powder.
[0124] <Synthesis Example 21> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P8 polymerized in Synthesis Example 8 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) with stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M8) as a black powder.
[0125] <Synthesis Example 22> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P9 polymerized in Synthesis Example 9 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M9) as a black powder.
[0126] <Synthesis Example 23> In a 100mL reaction flask equipped with a condenser, 0.90g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0g of P10 polymerized in Synthesis Example 10 dissolved in 16.40g of chloroform and 6.40g of ethanol was added using a dropping funnel. This mixture was stirred at 60°C for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M10) as a black powder.
[0127] <Synthesis Example 24> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P11 polymerized in Synthesis Example 11 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) with stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M11) as a black powder.
[0128] <Synthesis Example 25> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P12 polymerized in Synthesis Example 12 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate the polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M12) as a black powder.
[0129] <Synthesis Example 26> In a 100 mL reaction flask equipped with a condenser, 0.90 g of palladium acetate [manufactured by Wako Pure Chemical Industries, Ltd.] and 9.10 g of chloroform were charged and stirred until homogenous. To this solution, a solution of 1.0 g of P13 polymerized in Synthesis Example 13 dissolved in 16.40 g of chloroform and 6.40 g of ethanol was added using a dropping funnel. This mixture was stirred at 60° C. for 8 hours under a nitrogen atmosphere. After cooling to a liquid temperature of 30°C, this solution was poured into 341 g of an IPE / hexane solution (mass ratio 10:1) while stirring to precipitate a polymer / Pd particle composite. The precipitated polymer / Pd particle composite was filtered under reduced pressure and vacuum dried at 50°C to obtain 0.9 g of a Pd particle composite (M13) as a black powder.
[0130] Electroless plating primers were prepared by adding components (C) and (D) to the Pd particle composites M1 to M13 in the ratios shown in Table 1 below. The electroless plating primers containing M1 to M3, respectively, are comparative examples. The electroless plating primers containing M4 to M13, respectively, are examples.
[0131] [Table 1]
[0132] [Preparation of plating solution] <Preparation Example 1> In a 200mL beaker, 100mL of pure water, 17mL of Basic Printganth V (Atotech), 9mL of Copper Solution Printganth V (Atotech), 1.6mL of Starter Printganth PV (Atotech), 0.24mL of Stabilizer Printganth PV (Atotech), 3.2mL of Reducer Cu (Atotech), and 4mL of 18.5% by mass NaOH aqueous solution were charged, and pure water was added to make the total amount of the solution 200mL. This solution was stirred to make an electroless copper plating solution.
[0133] [Evaluation of plating deposition properties] Each of the electroless plating primers of Examples 1 to 10 and Comparative Examples 1 to 6 was bar-coated to a thickness of 6 μm on a polyimide (Kapton 100EN (registered trademark) manufactured by DuPont-Toray Co., Ltd.) substrate, and then heated at 80° C. for 5 minutes to form a coating film. This coating film was further dried by heating at 250° C. for 30 minutes. The resulting film was immersed in the electroless copper plating solution prepared in Preparation Example 1 for 10 minutes. The resulting plated substrate was then washed with water, and the condition of the metal plating film was visually evaluated. The evaluation results are summarized in Table 2 below.
[0134] <Evaluation criteria for plating deposition> ◯: Plating is uniformly deposited over the entire surface of the coating. ×: Plating was not uniformly deposited over the entire surface of the coating film.
[0135] [Table 2]
[0136] As shown in Table 2, the electroless plating primers of Examples 1 to 13 and Comparative Examples 1 to 3 had good plating deposition properties. On the other hand, the electroless plating primers of Comparative Examples 4 to 7 did not show any plating deposition.
Claims
1. An electroless plating undercoat agent for forming a metal plating film on a substrate by electroless plating treatment, comprising: (A) a copolymer containing a structural unit derived from a monomer a having at least one trifluoromethyl group and one radically polymerizable double bond in the molecule, and a structural unit derived from a monomer b having a metal dispersing group and one radically polymerizable double bond in the molecule; (B) metal fine particles, and (C) Solvent A primer comprising: The electroless plating primer, wherein the metal dispersing group is a substituent having a -C(=O)-N- moiety.
2. The primer according to claim 1 , comprising a complex in which the metal fine particles (B) are attached to or coordinated with metal dispersing groups in the copolymer (A).
3. 3. The base material according to claim 1, wherein the monomer a is a compound having either a vinyl group or a (meth)acryloyl group.
4. The primer according to claim 3 , wherein the monomer a is a compound represented by the following formula (1): 【Chemistry 1】 In formula (1), M represents a single bond, a carbonyloxy group, an amide group, or a phenylene group, J represents a linear or branched alkyl group having 1 to 10 carbon atoms and at least one trifluoromethyl group, R 6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
5. 3. The base material according to claim 1, wherein the monomer b is a compound having either a vinyl group or a (meth)acryloyl group.
6. The primer according to claim 5 , wherein the monomer b is a compound represented by the following formula (2) or (3): 【Chemistry 2】 (In formula (2), R 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; L represents O or N; R 2 is present only when L represents N and represents a hydrogen atom or R 1 and R 2 may, together with the atom to which they are attached, form a 4- to 6-membered cyclic amide. In formula (3), R 3 represents a hydrogen atom or a methyl group, R 4 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms which may be branched, an alkoxyl group having 1 to 10 carbon atoms which may be branched, or an alkoxylalkyl group having 1 to 10 carbon atoms which may be branched; L represents O or N; R 5 is present only when L represents N and represents a hydrogen atom or R 4 and R 5 may form, together with the atom to which they are attached, a 4- to 6-membered cyclic amide or a 4- to 6-membered cyclic imide.
7. 7. The primer according to claim 6, wherein the monomer b is N-vinylpyrrolidone, N-vinylacetamide or N-vinylformamide.
8. The primer according to any one of claims 1 to 7, wherein the monomer mixture that gives the copolymer (A) contains the monomer a in an amount that is 5 to 500% in molar ratio relative to the molar ratio of the monomer b.
9. The copolymer (A) further contains a structural unit derived from a monomer c having a crosslinkable group and one radically polymerizable double bond in the molecule, 9. The primer according to claim 1, wherein the crosslinkable group is an N-alkoxymethyl group, an N-hydroxymethyl group, an epoxy group which may have a substituent Q, an alicyclic epoxy group which may have a substituent Q, or an oxetane group which may have a substituent Q, wherein the substituent Q is an alkyl group having 1 to 4 carbon atoms which may be substituted with a halogen or a phenyl group.
10. The primer according to claim 9 , wherein the monomer c is a compound having either a vinyl group or a (meth)acryloyl group.
11. The primer according to claim 10, wherein the monomer c is a compound represented by the following formula (4): 【Chemistry 3】 (In formula (4), X represents a single bond, a carbonyloxy group, an amide group, or a phenylene group; Y represents an alkylene group having 1 to 6 carbon atoms, an oxyalkylene group having 1 to 6 carbon atoms, an optionally branched alkyl ether group having 1 to 6 carbon atoms, a thioalkylene group having 1 to 6 carbon atoms, or a thioalkyl ether group having 1 to 6 carbon atoms; Z represents a crosslinkable group; R 7 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
12. The primer according to any one of claims 9 to 11, wherein the monomer mixture that gives the copolymer (A) contains the monomer c in an amount that is 5 to 300% in molar amount relative to the number of moles of the monomer b.
13. The primer according to any one of claims 1 to 12, wherein the (B) metal microparticles are microparticles of at least one metal selected from the group consisting of iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), tin (Sn), platinum (Pt) and gold (Au).
14. The primer according to claim 13, wherein the metal fine particles (B) are palladium fine particles.
15. The primer according to any one of claims 1 to 14, wherein the (B) metal fine particles are fine particles having an average primary particle size of 1 to 100 nm.
16. The primer according to claim 1 , further comprising (D) a base resin having a non-radically polymerizable crosslinkable group.
17. The primer according to any one of claims 1 to 16, further comprising (E) a crosslinking agent.
18. 18. An underlayer for electroless metal plating, comprising a film containing the electroless plating undercoat agent according to claim 1.
19. A metal plating film formed on the underlayer of electroless metal plating according to claim 18.
20. A metal-coated substrate comprising a substrate, an underlayer of electroless metal plating according to claim 18 formed on the substrate, and a metal plating film formed on the underlayer of electroless metal plating.
21. A method for producing a metal-coated substrate, comprising the following steps (1) and (2): (1) Step: A step of applying the electroless plating primer according to any one of claims 1 to 17 onto a substrate to form a substrate layer for electroless metal plating on the substrate; (2) Step: A step of immersing the substrate on which the underlayer has been formed in an electroless plating bath to form a metal plating film on the underlayer.
Citation Information
Patent Citations
Electroless plating formation material, coating liquid for catalyst adhesion, electroless plating formation method, and plating method
JP2008214749A
Plating catalyst and method
JP2013155437A
Electroless plating primer including hyperbranched polymer and metallic microparticles
WO2012141215A1
Wiring forming method
WO2018151073A1
Electroless plating primer including polymer and metal fine particles
WO2019171985A1